A new meaning of the teaching practice: reflections on the teacher’s daily basis (2019)
This article seeks to reflect on the teaching practice of the professors (authors) of mathematics and natural sciences of the Juan José Rondón Educational Institution in Soatá (Colombia) to face questions, to critically, permanently and constantly self-assess their work, with the objective of giving a new meaning to these teaching practices, to materialize hybrid strategies to promote other interactions in the classroom. The research is developed in four phases that interact, taking into account the spiral of Carr and Kemmis, planning, action, observation and reflection, is developed from the socio-critical paradigm, has a unit of analysis of 28 students of eighth grade. In short, the teacher is expected to build awareness about the importance of giving a new meaning to their work, think, analyze, understand and, from this interpretation, generate changes that affect both the improvement of their performance and the welfare of the students in terms of learning. The (re) significance part of the reflection and self-criticism, it gives meaning to what is done and this sense is new; that is to say, each of the activities is recreated, re-thought and re-elaborated, lookingfor other dynamics regarding the didactic component of the teaching practice in benefit of the students’ learning process.